Role of Technology (AI) in Enhancing Scalability and Impact of Social Enterprises - Bhat, Sahana P (Digital Repository of Theses, 2024)
The use of technology in social enterprises has recently emerged as a crucial factor in balancing an organization’s social objectives with its sustainability. This research investigates how technological advancements, particularly Artificial Intelligence (AI), enhance the effectiveness and outreach of social enterprises. Despite the growing interest in this area, there is a notable gap in understanding how AI can be specifically applied to maximize both operational productivity and community impact in social enterprises. My research aims to address this gap by exploring the effects of modern technologies like AI on business operations, community impact, and the potential for organizational expansion. By employing assorted-methods research approach-qualitative interviews, quantitative surveys, and inferential statistics were used to investigate the associations between the level of technology adoption and the outcome measures of interest, such as operational efficiency, scalability, and social impact. These statistical tests were employed to uncover significant predictors, with the main emphasis on establishing the strength and direction of these relationships. The qualitative part of the data, based on the interviews conducted with the social entrepreneurs, is analyzed through thematic analysis. The main results indicate a strong consensus among respondents that AI and modern technologies significantly enhance the development and efficacy of social enterprises. These technologies improve organizational operations, leading to more efficient processes and reduced resource consumption, thereby allowing enterprises to dedicate more efforts to their missions. However, the study also highlights several challenges associated with technology integration, including technological infrastructure issues, lack of resources, difficulties in implementing changes, shortage of qualified personnel, and high adoption costs. These obstacles need to be addressed to fully reap the benefits of technology in social enterprises. In conclusion, the research demonstrates that AI and modern technologies are powerful tools that can drive substantial social transformation by enabling social enterprises to operate more strategically, engage on a global scale, and make a significant impact. For further research, it is recommended to explore the adoption of AI to enhance effectiveness, develop AI-based models for innovation, and focus on educating both workers and beneficiaries. Additionally, attention should be given to overcoming financial limitations and implementing technology in stages to ensure a smooth transition.